1983
DOI: 10.1029/ja088ia01p00096
|View full text |Cite
|
Sign up to set email alerts
|

Electron velocity distributions near the Earth's bow shock

Abstract: A survey of two-dimensional electron velocity distributions, f(¾), measured near the earth's bow shock using Los Alamos/Garching plasma instrumentation aboard ISEE 2 is presented. This survey provides clues to the mechanisms of electron thermalization within the shock and the relaxation of both the upstream and downstream velocity distributions. First, near the foreshock boundary, fluxes of electrons having a power law shape at high energies backstream from the shock. Although most often they appear as a monot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
209
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 425 publications
(224 citation statements)
references
References 36 publications
15
209
0
Order By: Relevance
“…Interestingly, Fig. 4 shows that features previously reported with the ramp, e.g., the beam vestige of the solar wind peak [28], are present only in the more gradual initial rise that precedes the steep ramp. That beam has been totally eroded by the time this electron scale ramp is encountered.…”
Section: Results and Conclusionmentioning
confidence: 77%
See 1 more Smart Citation
“…Interestingly, Fig. 4 shows that features previously reported with the ramp, e.g., the beam vestige of the solar wind peak [28], are present only in the more gradual initial rise that precedes the steep ramp. That beam has been totally eroded by the time this electron scale ramp is encountered.…”
Section: Results and Conclusionmentioning
confidence: 77%
“…3 shows that both the parallel and perpendicular electron temperatures closely track the steep rise in magnetic field, with half the electron heating taking place on a scale of 17.3 km, corresponding to 6.4 electron inertial lengths and a small fraction (0.15) of an ion inertial length. Although much of the electron dynamics is linked to the DC electric and magnetic fields within the ramp [8,24,28,29] and is therefore reversible, the fact that both T e and T e⊥ rise together suggests an infla- tion of the particle phase space distribution that is not reversible, due primarily to the filling in and/or entrapment of electrons in regions of phase space that would otherwise be inaccessible. This infilling can be seen in the cuts of the distributions shown in Fig.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…The resulting reduced distributions close to the leading edge of the foreshock display a pronounced peak with a sharp cutoff near the cutoff velocity. While individual observational examples of discernible "bumps" in distributions that may be unstable have been reported [Fitzenreiter et al, 1984[Fitzenreiter et al, , 1990, only stable distributions with "plateaus" are commonly observed [Feldman et al, 1982[Feldman et al, , 1983, which questions the temporal persistence of the bump-on-tail distributions.…”
Section: Fitzenreiter Et Al [1990] Developed a 3-d Analyticalmentioning
confidence: 99%
“…On the other hand, space plasma observations indicate the presence of ion and electron populations which are not in thermodynamic equilibrium (Asbridge et al, 1968;Feldman et al, 1983; Correspondence to: F. Verheest (frank.verheest@ugent.be) Lundin et al, 1989;Futaana et al, 2003). Often, these nonthermal velocity distributions include a ring structure, and the simplest analytical way to model such effects is by the Cairns distribution (Cairns et al, 1995).…”
Section: Introduction and Basic Formalismmentioning
confidence: 99%